135 Community crèche is a measure to prevent child injuries: challenges and measures for improvement. (1st September 2016) - Ashrafi, Rabbeya; Baset, Kamran Ul; Bhuiyan, Al-Amin; Rahman, Aminur
Abstract : Background: Injury is the leading killer of children in Bangladesh. Anchal (community crèche) is an effective intervention to prevent injuries among children under 5. Through SoLiD project 1, 600 Anchal s are in place in three sub-districts in Bangladesh. The objectives of the Anchal are to provide supervision and early childhood development stimulations (ECD) to the children. A local trained caregiver supervises 20–25 children, 9 to 59 months old, during 9 a.m. to 1 p.m., six days a week. Although it was found effective, during its implementation phase several challenges were noticed. The study was conducted to identify challenges and means to overcome those to improve the Anchal activities. Methods: In-depth interviews were conducted with Anchal caregivers, their supervisors and trainers. Focus group discussions were conducted with the Anchal childrens' mother. The study was conducted in Manohardi sub-distict during November 2015. Results: Decay of knowledge and skills after 2–3 months of training, lack of formal certification and inappropriate selection of women as Anchal caregivers, enrollment of small children (less than 12 months) were the important challenges. Reluctance of parents to send children at the Anchal in proper time, failure to engage children in various ECD activities, ineffective conduction of parents and community leaders meeting by the Anchal caregivers, insufficient accommodation and poor supply of logistics for children were also the important challenges. The suggestion for improvement were to recruit caregivers as per standard criteria, provide them refreshers training at three months interval, train them on effective conduction of parents and community leaders meeting, provide formal certificate and ensure regular supply of logistics. Conclusions: The identified challenges are needed to be addressed by utilising the suggestions obtained from the IDIs and FGDs to make the Anchal intervention more effective in preventing childhood injuries.